DEVELOPMENT OF NANOPARTICULATE DRUG DELIVERY SYSTEM FROM MARINE SOURCE AGAINST HUMAN IMMUNODEFICIENCY VIRUS: MARINE STUDY - N, HARIKRISHNAN; S MOHAMIED, ANAS; S, GEJALAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Nanotechnology techniques are a creation and exploitation of materials, devices, and systems through the control of matter on the nanometer length scale, i.e., involvement of atoms, molecules, and supramolecular structures. Every existing treatment modalities against human immunodeficiency virus (HIV) offer a marginal increase in the life expectancy as chitosan was converted to its derivative aminoethyl chitosan by chemical method evaluated for anti-HIV activity. Methods: Isolation of chitosan from crab shell by chemical method involves four basic steps; protein separation, calcium carbonate separation, deproteinization, and demineralization. Results: The results revealed the anti-HIV activity of the prepared nanoparticulate system. Cytotoxicity assay of the nanoparticulate system was carried out and the cytotoxic concentration 50% (CC50) value was found to be 38.07±1.42 μg/ml, indicating that the nanoparticulate system is not cytotoxic. HIV-1 infection inhibition assay was carried out and the nanoparticulate system showed excellent inhibitory activity with a half-maximal inhibitory concentration (IC50) value of 3.75±0.57 μg/ml. Conclusions: It concludes, the CC50 and inhibitory concentration 50% IC50 values, the selectivity index of the nanoparticle was found to be 17.65 compared to the standard drug nevirapine (82.32), indicating the usefulness of the formulated nanoparticulate system as potential anti-HIV agent.